Wife's Role In Overcoming Domestic Problems - Rahmat Kurniawan*; Fatimah Fatimah (Universitas Syiah Kuala, 2023)
The household is the basic unit of society, with duties and responsibilities carried out by husbands and wives. This research emphasizes the importance of the wife's role in maintaining family balance and harmony. One of the key aspects emphasized is effective communication; the ability to listen actively and express opinions tactfully contributes significantly to solving family problems. Wives' involvement in financial aspects, both in terms of contribution and financial management, plays an important role in addressing family economic problems. Gender equality, teamwork between husband and wife, and wife's financial independence were found to be key factors in ensuring harmony and balance in the household.